Incidence of Intraoperative Hypersensitivity Reactions: A Registry Analysis. (March 2015) - Saager, Leif; Turan, Alparslan; Egan, Cameron; Mascha, Edward J.; Kurz, Andrea; Bauer, Maria; Besson, Hervé; Sessler, Daniel I.; Hesler, Brian D.
Abstract : Background: Previously reported incidences for intraoperative hypersensitivity reactions vary more than 15-fold. The goal was to determine the incidence of intraoperative hypersensitivity events at a U.S. surgical center. Methods: With institutional review board (Cleveland, Ohio) approval and waiver of written/informed consent, the anesthesia records of adult patients undergoing noncardiac surgery from 2005 to 2011 at the Cleveland Clinic were queried using a novel electronic search protocol developed to identify potential hypersensitivity reactions: cardiovascular collapse defined as systolic arterial blood pressure less than 50 mmHg; administration of epinephrine; administration of diphenhydramine; physician comments in the anesthesia record suggestive of hypersensitivity reactions; laboratory tests for histamine, tryptase, or immunoglobulin-E within 24 h of surgery; and International Classification of Diseases, Ninth Revision, codes suggestive of hypersensitivity reactions. Each electronically identified candidate chart was evaluated by an adjudication committee. Hypersensitivity reactions were graded on a 5-point severity scale. From these data, the authors determined the proportion of operations having adjudicated hypersensitivity reactions, and calculated the 95% exact binomial CI. Results: Among 178, 746 records, 4, 008 charts were identified by the search strategies. After adjudication, 264 hypersensitivity cases were identified. The overall incidence of hypersensitivity reactions was 1:677 surgeries, corresponding to 15 (95% CI, 13 to 17) cases per 10, 000 operations. The incidence of severe hypersensitivity reactions (grades 3 to 5) was 1:4, 583, corresponding to 2 (95% CI, 2 to 3) cases per 10, 000 operations. Conclusions: The incidence of severe hypersensitivity reactions was similar to previous reports. However, the overall incidence of hypersensitivity reactions was much greater than reported elsewhere, possibly because of a comprehensive search strategy. Abstract : A novel methodology combining electronic search strategies and clinical adjudication was used to identify occurrences of hypersensitivity reactions. The overall incidence of hypersensitivity reactions identified from the electronic records of 178, 746 procedures performed on 120, 242 patients was 1 in 677 and that of anaphylaxis was 1 in 4, 583. The incidence of anaphylaxis was similar to that reported in previous studies but that of hypersensitivity reactions was nearly seven times higher.